MODEL BADAI IONOSFER INDONESIA TERKAIT BADAI GEOMAGNET (INDONESIA IONOSPHERIC STORM MODEL RELATED TO GEOMAGNETIC STORM) - Anwar Santoso; Mira Juangsih; Sri Ekawati; Iyus Edi Rusnadi; Anton Winarko; Siska Filawati; Dadang Nurmali (Jurnal Sains Dirgantara, 2017)
Knowledge about the ionospheric response to the geomagnetic storms is needed to support SWIFtS activity in Space Science Center-LAPAN. However, it is difficult to predict its behavior. As an approach, it needs a model of the ionospheric response to geomagnetic storms. In this paper, the modeling of the Indonesia ionospheric storms to the geomagnetic storm was done by modifying the global empirical models developed by Araujo-Pradere. By using ap index data, Dst index, and foF2 ionosphere from BPAA Sumedang of 2005-2015, it was obtained the Indonesia ionospheric storms model related to the geomagnetic storm. The analysis result showed that the Sumedang ionospheric storms model had a deviation or error < 40% of the data. Therefore it can be concluded that this models can be used to support the SWIFtS activity in Space Science Center-LAPAN for future space weather conditions.  AbstrakPengetahuan tentang respon ionosfer terhadap badai geomagnet sangat diperlukan untuk mendukung kegiatan SWIFtS di Pusat Sains Antariksa-LAPAN. Namun, sulit diprediksi perilakunya. Sebagai pendekatan, diperlukan sebuah model respon ionosfer terhadap badai geomagnet. Dalam makalah ini, dilakukan pemodelan badai ionosfer Indonesia terkait badai geomagnet dengan memodifikasi model empiris global yang telah dikembangkan oleh Araujo-Pradere. Dengan menggunakan data indeks ap, indeks Dst dan foF2 ionosfer BPAA Sumedang tahun 2005-2015 diperoleh model badai ionosfer regional Indonesia terhadap badai geomagnet. Dari analisis disimpulkan bahwa model badai ionosfer Sumedang tersebut memiliki simpangan atau kesalahan < 40% terhadap data. Hal ini menunjukkan bahwa model badai ionosfer Sumedang tersebut dapat dipergunakan untuk mendukung kegiatan SWIFtS di Pusat Sains Antariksa-LAPAN sebagai bahan pertimbangan dalam memprediksi kondisi cuaca antariksa akan datang.